A prospective cohort study on lactation status and breastfeeding challenges in mothers giving birth to preterm infants - Dingding Dong; Xifang Ru; Xiaofang Huang; Tian Sang; Shan Li; Ying Wang; Qi Feng (BMC, 2022)
Abstract Background Mothers of preterm infants face many challenges in breastfeeding, especially regarding lactation. This study aimed to investigate the lactation status and challenges in breastfeeding faced by preterm infants' mothers. Methods We approached 124 mothers who gave birth to preterm infants between 26 May and 31 October 2018 in a tertiary hospital in China. Lactation status and challenges in breastfeeding on day 7 postpartum, at discharge of infants, 2 weeks post-discharge, and 3 months of corrected age were collected using questionnaires. The area under the receiver operating characteristic (ROC) curve for expressed milk volume on day 7 postpartum for predicting expressed milk volume ≥ 300 mL/d at discharge was calculated. Logistic regression analyses were performed to identify factors associated with delayed lactogenesis II onset and continuation of breastfeeding at 3 months of corrected age. Results Seventy mothers were enrolled, and 51.4% had delayed lactogenesis II. Multivariate logistic regression analysis revealed that older maternal age (aOR = 1.19; 95% CI: 1.01, 1.40) and first live birth (aOR = 4.81; 95% CI 1.43, 16.18) were significant independent predictors of delayed lactogenesis II. Mothers with delayed lactogenesis II had significantly lower expressed milk volume (day 7 postpartum: 160.0 mL vs. 300.0 mL, U = 328.50, p = 0.001; at discharge: 425.0 mL vs. 612.5 mL, U = 372.00, p = 0.005), with a lower proportion of exclusive breastfeeding in their infants (at discharge: 33.3% vs. 69.8%, χ 2  = 12.39, df = 1, p < 0.001; 3 months of corrected age: 17.8% vs. 52.8%, χ 2  = 11.03, df = 1, p = 0.001). The ROC showed that expressed milk volume > 190 mL/d on day 7 postpartum significantly predicted expressed milk volume ≥ 300 mL/d at discharge. Insufficient human milk was the main reason for breastfeeding discontinuation at 3 months of corrected age. Twins were less likely to continue breastfeeding at 3 months of corrected age (aOR = 0.27; 95% CI 0.09, 0.86). In singleton infants, mother's own milk ≥50% of total milk uptake at 2 weeks post-discharge (aOR = 32.66; 95% CI 3.00, 355.25) was an independent predictor of continuous breastfeeding at 3 months of corrected age. Feeding complications in infants, poor breastfeeding technique, and low milk output are the main challenges in breastfeeding. Conclusion Interventions to improve early postpartum lactation and breastfeeding techniques may increase breastfeeding adoption in mothers of preterm infants.